Mask Technology: Masks Theater (Nau) a model - Sulaiman, ZaidSalim (Al-Adab Journal, 2020)
Mask his presence record in almost all civilizations and cultures successive particularly during liturgical celebrations and religious, as this presence in everyday life seemed then go to the theater to become an expression of aesthetically pleasing in terms of formation Representative and other aesthetic of the product employs theatrical performances throughout the periods of the history of the theater. Our selection of the subject (the mask technique) necessarily imposes an orientation aesthetic choices and techniques related to it and different from other aesthetics on the level of representation of actor such as animation, sound, speech and gesture and the rest of the display elements of fashion and decoration and others. Hence our study to look at the mask techniques, and taken from the scene (Nau) Japanese have a model.